Terapi Pemberian Besi pada Penderita Anemia Defisiensi Besi - Kapoh, Sabatika R; Rotty, Linda W. A.; Polii, Efata B. I. (Universitas Sam Ratulangi, 2021)
Abstract: Iron deficiency anemia (IDA) is caused by deficiency of iron needed for hemoglobin synthesis. Based on WHO data 2011, of 100% cases of patients with severe anemia, there were 50% of pregnant women, 49% of non-pregnant women, and 42% of children suffered from iron deficiency. Other literatures mentioned about 2-5% of adult men and post menopause women were diagnosed as iron deficiency anemia in developed countries. This study was aimed to determine the relationship between iron therapy in patients and iron deficiency anemia. This was a literature review study, summarizing the results of studies that included iron therapy to iron deficiency anemia patients. The results showed a positive result of iron therapy among iron deficiency anemia patients. In conclusion, there is an increase in hemoglobin among iron deficiency anemia patients after being given iron therapy.Keywords: iron deficiency anemia, iron therapyÂ Â Abstrak: Anemia defisiensi besi (ADB) disebabkan oleh kekurangan zat besi yang dibutuhkan untuk sintesis hemoglobin. Berdasarkan data dari WHO (World Health Organization) tahun 2011, dari 100% kasus penderita anemia berat yang dilaporkan, diperkirakan 50% wanita hamil, 49% wanita tidak hamil, dan 42% kasus anak penderita anemia didapatkan berkaitan dengan kekurangan zat besi. Data lain menyebutkan sekitar 2-5% pria dewasa dan wanita pasca menopause mengalami ADB di negara maju. Penelitian ini bertujuan untuk mengetahui hubungan pemberian besi pada pasien anemia defisiensi besi. Jenis penelitian ialah literature review. Hasil penelitian ini menunjukkan hasil positif pemberian terapi besi pada pasien anemia defisiensi besi. Simpulan penelitian ini ialah terdapat peningkatan hemoglobin pada pasien anemia defisiensi besi setelah diberikan terapi besi.Kata kunci: anemia defisiensi besi, terapi besi